Nuclear proteasomal degradation of Saccharomyces cerevisiae inorganic pyrophosphatase Ipp1p, a nucleocytoplasmic protein whose stability depends on its subcellular localization - Serrano-Bueno, Gloria; Madroñal, Juan Manuel; Manzano-López, Javier; Muñiz, Manuel; Pérez-Castiñeira, José Román; Hernández, Agustín; Serrano, Aurelio (Biochimica et biophysica acta. Molecular cell research, 2019)
Inorganic pyrophosphate (PPi) is an abundant by-product of cellular metabolism. PPi-producing reactions take place in the nucleus concurrently with reactions that use PPi as a substrate. Saccharomyces cerevisiae possesses two soluble pyrophosphatases (sPPases): Ipp1p, an essential and allegedly cytosolic protein, and Ipp2p, a mitochondrial isoenzyme. However, no sPPase has yet been unambiguously described in the nucleus. In vivo studies with fluorescent fusions together with activity and immunodetection analyses demonstrated that Ipp1p is a nucleocytoplasmic protein. Mutagenesis analysis showed that this sPPase possesses a nuclear localization signal which participates in its nuclear targeting. Enforced nucleocytoplasmic targeting by fusion to heterologous nuclear import and export signals caused changes in polypeptide abundance and activity levels, indicating that Ipp1p is less stable in the nucleus that in the cytoplasm. Low nuclear levels of this sPPase are physiologically relevant and may be related to its catalytic activity, since cells expressing a functional nuclear-targeted chimaera showed impaired growth and reduced chronological lifespan, while a nuclear-targeted catalytically inactive protein was not degraded and accumulated in the nucleus. Moreover, nuclear proteasome inhibition stabilized Ipp1p whereas nuclear targeting promoted its ubiquitination and interaction with Ubp3p, a component of the ubiquitin-proteasome system. Overall, our results indicate that Ipp1p is nucleocytoplasmic, that its stability depends on its subcellular localization and that sPPase catalytic competence drives its nuclear degradation through the ubiquitin-proteasome system. This suggests a new scenario for PPi homeostasis where both nucleocytoplasmic transport and nuclear proteasome degradation of the sPPase should contribute to control nuclear levels of this ubiquitous metabolite. •It is generally believed that the main yeast sPPase Ipp1p is a cytoplasmic enzyme.•We provide evidence indicating that Ipp1p is a nucleocytoplasmic protein which undergoes nuclear proteasomal degradation.•Nucleocytoplasmic transport provides an added level of sPPase spatial regulation which should eventually control PPi pools of cell nucleus and cytosol.